Exposure to surgery is associated with better long‐term outcomes in patients admitted to Swedish intensive care units. Issue 8 (28th April 2020) - Jawad, Monir; Baigi, Amir; Chew, Michelle
Abstract : Background: Long‐term outcomes of patients admitted to intensive care units (ICUs) after surgery are unknown. We investigated the long‐term effects of surgical exposure prior to ICU admission. Methods: Registry‐based cohort study. The adjusted effect of surgical exposure for mortality was examined using Cox regression. Secondary analysis with conditional logistic regression in a case‐control subpopulation matched for age, gender, and Simplified Acute Physiology Score III (SAPS3) was also conducted. Results: 72 242 adult patients (56.9% males, median age 66 years [IQR 50‐76]), admitted to Swedish ICUs in 3‐year (2012‐2014) were followed for a median of 2026 days (IQR 1745‐2293). Cardiovascular diseases (17.5%), respiratory diseases (15.8%), trauma (11.2%), and infections (11.4%) were the leading causes for ICU admission. Mortality at longest follow‐up was 49.4%. Age; SAPS3; admissions due to malignancies, respiratory, cardiovascular and renal diseases; and transfer to another ICU were associated with increased mortality. Surgical exposure prior to ICU admission (adjusted hazard ratio [aHR] 0.90; 95% CI 0.87‐0.94; P < .001), admissions from the operation theatre (aHR 0.94; CI 0.90‐0.99; P = .022) or post‐anaesthesia care unit (aHR 0.92; CI 0.87‐0.97; P  = .003) were associated with decreased mortality. Conditional logistic regression confirmed the association between surgical exposure and decreased mortality (adjusted odds ratio 0.82; CI 0.75‐0.91; P  < .001). Conclusions: Long‐term ICU mortality was associated with known risk factors such as age and SAPS3. Transfer to other ICUs also appeared to be a risk factor and requires further investigation. Prior surgical exposure was associated with better outcomes, a noteworthy observation given limited ICU admissions after surgery in Sweden.